Labouring for leisure? Achieving work life balance through compressed working weeks - Brown, Kerry; Bradley, L.; Lingard, H.; Townsend, K.; Ling, S. (Routledge, 2011)
Flexible work practices spreading work times across the entire week have reduced the time to engage in leisure activities and for some have compounded the problem of a lack of defined break between work weeks. This study examines time spent outside of the workplace through a multiple case study of working time and leisure in the construction industry. A framework of synchronous leisure is used to examine the interplay of work and non-work arrangements. The effects of changing work arrangements to deliver a longer break between working weeks and the consequent impact on leisure activities are analysed. Interviews and focus groups across four construction sites revealed that while leisure is important to relieve fatigue and overwork, a work schedule allowing a long break between working weeks, specifically on a weekend, enables workers to achieve synchronous time, particularly with family, and improves work-life balance satisfaction. It was found that a well-defined break across a weekend also offers the opportunity to synchronize schedules with others to spend time away on short breaks.